Construction of multi-substituted pyrazoles via potassium carbonate-mediated [3 + 2] cycloaddition of in situ generated nitrile imines with cinnamic aldehydes. Issue 21 (29th April 2022) - Li, Mei-Mei; Huang, Hui; Tian, Wanrong; Pu, Yiru; Zhang, Chaozheng; Yang, Jirui; Ren, Qing; Tao, Feiyan; Deng, Yun; Lu, Jun
Abstract : A highly efficient potassium carbonate-mediated [3 + 2] cycloaddition reaction of hydrazonoyl chlorides with cinnamic aldehydes to furnish multi-substituted pyrazoles under nontoxic and mild conditions has been developed. Abstract : A highly efficient potassium carbonate-mediated [3 + 2] cycloaddition reaction of hydrazonoyl chlorides with cinnamic aldehydes to furnish multi-substituted pyrazoles under nontoxic and mild conditions has been developed. A plausible stepwise cycloaddition reaction mechanism is proposed. This protocol featured broad substrate coverage, good functional group tolerance, wide scalability, and operational simplicity, as well as conveniently constructed pyrazole scaffolds.